2015
DOI: 10.18632/aging.100765
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific autophagy responses to aging and stress in C. elegans

Abstract: Cellular function relies on a balance between protein synthesis and breakdown. Macromolecular breakdown through autophagy is broadly required for cellular and tissue development, function, and recovery from stress. While Caenorhabditis elegans is frequently used to explore cellular responses to development and stress, the most common assays for autophagy in this system lack tissue-level resolution. Different tissues within an organism have unique functional characteristics and likely vary in their reliance on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
62
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 80 publications
12
62
1
Order By: Relevance
“…Consistent with our observation that tald-1(RNAi) induces nuclear localization of HLH-30, we found that components of the autophagy pathway [62] were upregulated in a HLH-30-dependent fashion, including lgg-1 ( LC3 homolog), sqst-1 (p62/ SQSTM1 homolog), lmp-1 ( LAMP1 homolog), and lysosomal subunit vha-17 (Fig 6E and 6F). In addition, autophagic flux is increased by tald-1(RNAi) (Fig 6G and 6H), as measured by a recently described LGG-1 reporter of lysosomal protease activity [67]. The reporter consists of LGG-1 tagged with two fluorescent proteins containing a flexible protease-sensitive linker.…”
Section: Resultsmentioning
confidence: 92%
“…Consistent with our observation that tald-1(RNAi) induces nuclear localization of HLH-30, we found that components of the autophagy pathway [62] were upregulated in a HLH-30-dependent fashion, including lgg-1 ( LC3 homolog), sqst-1 (p62/ SQSTM1 homolog), lmp-1 ( LAMP1 homolog), and lysosomal subunit vha-17 (Fig 6E and 6F). In addition, autophagic flux is increased by tald-1(RNAi) (Fig 6G and 6H), as measured by a recently described LGG-1 reporter of lysosomal protease activity [67]. The reporter consists of LGG-1 tagged with two fluorescent proteins containing a flexible protease-sensitive linker.…”
Section: Resultsmentioning
confidence: 92%
“…Differences in neuronal and muscular autophagy in ALS FUS models may arise in part from tissue-specific variations in basal autophagy. Indeed, two previous studies showed marked differences in C. elegans neuronal and muscular autophagy [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…LGG LGG-1 protein levels by Western Blot permits the quantitation of neuronal autophagy flux [36]. We found that ALS fust-1 alleles decreased the relative ratio of neuronal mFP to fulllength dFP::…”
Section: Knock-in Animals Show Impaired Autophagy In Motor Neurons Anmentioning
confidence: 90%
See 2 more Smart Citations